ANALISIS BESARAN UPAH DALAM MENINGKATKAN KESEJAHTERAAN KARYAWAN HARIAN LEPAS PADA PT. GUNTA SAMBA - Ali; Aji Ratna Kusuma; Rizkiawan (Tinta Nusantara 2018 Vol.1, 2020)
The purpose of this study was to examine and analyze the amount of wages provided by the company to improve the welfare of daily casual employees in accordance with this study entitled "Analysis of Wages in Improving the Welfare of Daily Casual Employees at PT Gunta Samba". Data was collected through the distribution of questionnaires, the sample used in this study was 75 daily freelance employees at PT Gunta Samba. Overall, the welfare indicators provided by the type of economy and services are quite good in terms of improving the welfare of daily casual employees at PT Gunta Samba